Pengaruh Ukuran Perusahaan dan Leverage terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Intervening - Octaviany, Ayu; Hidayat, Syamsul; Miftahudin, Miftahudin (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2019)
The company is basically established to create added value, especially in generating profits. But in general the company is not only oriented towards achieving maximum profit, but also trying to increase the value of the company and the prosperity of its owners by maximizing stock prices. High stock prices make the value of the company also high and increase market confidence in the company's prospects in the future. Company value can be influenced by several factors, including Company Size, Leverage and Profitability. The purpose of this study was to determine the effect of Company Size, Leverage and Profitability on Company Value and to determine the effect of Company Size and Leverage on Company Value through Profitability. The data analysis technique used is the Partial Least Square (PLS) model. Sampling was taken using purposive sample method. A total of 8 Food and Beverage manufacturing companies in the 2013-2017 period were sampled. The results of this study indicate that Company Size has a significant effect on Profitability but has no effect on Company Value. Leverage has no significant effect on Company Value but has a significant effect on Company Value. Profitability is able to mediate the influence of firm size on company value. But profitability is not able to mediate the influence of leverage on Company Value.